Cerebrovascular diseases in ADHD patients with metabolic comorbidities: a retrospective cohort study - Sarah Krieg; Andreas Krieg; Karel Kostev (BMC Psychiatry)
Abstract Background ADHD is associated with several health outcomes, but its long-term cerebrovascular associations, particularly in adults with metabolic conditions, remain poorly understood. Methods A retrospective cohort analysis was performed using the Disease Analyzer database (IQVIA) and included adults with ADHD which were compared to a propensity score matched non-ADHD cohort. The 10-year incidence of acute ischemic stroke (AIS) or transient ischemic attack (TIA) was analyzed using Kaplan-Meier curves and univariable conditional Cox regression models with hazard ratios (HRs) and 99% confidence intervals (CIs). Results Among 8,943 ADHD patients and 44,660 controls, 1.7% of ADHD patients and 1.2% of controls experienced AIS or TIA (log-rank test, p = 0.006). In the regression analysis, there was a significant association between ADHD and subsequent TIA or AIS in the total population (HR: 1.69; 99% CI:1.13-2.51). This association was stronger and significant in subgroups of patients aged >45 years (HR: 2.34; 99% CI: 1.43-3.81) and those with obesity (HR: 1.86; 99% CI: 1.22-2.83), hypertension (HR: 2.18; 99% CI: 1.19-3.97), or dyslipidemia (HR: 2.89; 99% CI: 1.48-5.52). Conclusion ADHD in adults, particularly those over 45 years of age and those with metabolic comorbidities, is associated with an increased risk of cerebrovascular disease. Further research is needed to confirm these associations and to explore the underlying mechanisms.